Evaluation of laparoscopic forceps jaw contact pressure and distribution using pressure sensitive film. (7th October 2019) - Zhu, Rui; Maréchal, Maxime; Yamamoto, Ikuo; Lawn, Murray John; Nagayasu, Takeshi; Matsumoto, Keitaro
Abstract: In this study, the authors used the Fujifilm Prescale Pressure Measuring System to measure the contact pressure and distribution at the jaws of laparoscopic grasping forceps. This data was then correlated with measured pressures at the forceps handles to understand the relationship between the surgeon's actuating pressure and that on the organ being manipulated. The purpose of this study is to create a database of tactile information to provide guidelines in defining minimally invasive surgery (MIS). This is expected to be important as today's society continues to progress in the use of automation, IoT, AI and MIS. In order to achieve the above, the authors developed an experimental device consisting of an actuator, a load cell and an MCU to stably actuate and control the handle side of grasping forceps. Target organs were simulated using triangular prisms of various silicone rubber materials. The experimental method involved actuating the handle side with preset pressure values for fixed time periods and using sensitive film to measure the pressure at the forceps tip. The film data was then scanned, processed and analyzed.